The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/jcm8040545
|View full text |Cite
|
Sign up to set email alerts
|

Can Tumor-Infiltrating Lymphocytes (TILs) Be a Predictive Factor for Lymph Nodes Status in Both Early Stage and Locally Advanced Breast Cancer?

Abstract: The status of axillary lymph nodes is an important prognostic factor in the outcome of breast cancer tumors. New trials changed the attitude towards axillary clearance. In the era of development of new immune therapies for breast cancer, it is important to identify a biomarker that can predict lymph node status. Tumor-infiltrating lymphocytes (TILs) are a valuable indicator of the immune microenvironment that plays the central role in new anticancer drugs. Although the correlation between TILs and response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
0
14
1
2
Order By: Relevance
“…Our hypothesis was that the TIL density may be a predictor of SLNM. The correlation between TILs and lymph node metastasis has been reported in gastric cancer, melanoma, and breast cancer [31][32][33]. A study on breast cancer examined 76 patients who underwent surgery first and 96 patients who underwent preoperative chemotherapy, and it reported that there was a correlation between TILs and lymph node metastasis in both groups.…”
Section: Discussionmentioning
confidence: 94%
“…Our hypothesis was that the TIL density may be a predictor of SLNM. The correlation between TILs and lymph node metastasis has been reported in gastric cancer, melanoma, and breast cancer [31][32][33]. A study on breast cancer examined 76 patients who underwent surgery first and 96 patients who underwent preoperative chemotherapy, and it reported that there was a correlation between TILs and lymph node metastasis in both groups.…”
Section: Discussionmentioning
confidence: 94%
“…Our hypothesis was that the TIL density may be a predictor of SLNM. The correlation between TILs and lymph node metastasis has been reported in gastric cancer, melanoma, and breast cancer [31][32][33]. A study on breast cancer examined 76 patients who underwent surgery rst and 96 patients who underwent preoperative chemotherapy, and it reported that there was a correlation between TILs and lymph node metastasis in both groups.…”
Section: Discussionmentioning
confidence: 93%
“…Our hypothesis was that the TIL density may be a predictor of SLNM. The correlation between TILs and lymph node metastasis has been reported in gastric cancer, melanoma, and breast cancer [28][29][30]. A study on breast cancer examined 76 patients who underwent surgery first and 96 patients who underwent preoperative chemotherapy, and it reported that there was a correlation between TILs and lymph node metastasis in both groups.…”
Section: Discussionmentioning
confidence: 94%